2020
DOI: 10.1002/app.49728
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties, rheological behaviors, and phase interaction of nylon 11/polypropylene blends by in situ reactive compatibilization and dispersion through polyhydroxybutyrate

Abstract: The current research discusses the reactive compatibilization of nylon 11 (PA11) and polypropylene (PP) using maleic anhydride grafted PP (PP-g-MA) through an extruder. PP phase is dispersed in PA11 by coalescence and droplet break-up mechanism by using polyhydroxybutyrate (PHB) as a dispersion agent that induces uniform interaction between the blend components. The reactive compatibilization ensures the mixing of polymers, and the consistent interaction of phases is controlled by dispersion. All of the blends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(124 reference statements)
1
1
0
Order By: Relevance
“…The increase in values is logical in this case, because the degradation of the material means cleavage and shortening of the macromolecular chains, which results in an increase in the material’s fluidity. This behavior was in agreement with data observed by Gadgeel et al [ 22 ] and Chen et al [ 23 ].…”
Section: Evaluation Of Results and Discussionsupporting
confidence: 93%
“…The increase in values is logical in this case, because the degradation of the material means cleavage and shortening of the macromolecular chains, which results in an increase in the material’s fluidity. This behavior was in agreement with data observed by Gadgeel et al [ 22 ] and Chen et al [ 23 ].…”
Section: Evaluation Of Results and Discussionsupporting
confidence: 93%
“…In order to endow PA10,12 with high impact strength, attempts have been made to exploit methods to toughen nylons, e.g. classical copolymerization, 6 polymer blending, [7][8][9] novel core-shell structure development 2,10 and plasticizing. 11,12 Zhao et al 13 reported that a brittle to ductile transition occurred when 15 wt% rubber was used in a rubber-modified nylon system.…”
Section: Introductionmentioning
confidence: 99%